Caffeine intake and pregnancy outcomes: a meta-analytic review Consumo de cafeína na gravidez e desfechos perinatais - Iná S. Santos; Cesar Gomes Victora; Sharon Huttly; Saul Morris (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 1998)
Epidemiological publications on the relationship of caffeine to birth weight and duration of human pregnancy, from 1966 to 1995, were searched through Medline. Each study was treated as the stratification variable, and its weight in the weighted average was proportional to the inverse of its variance. Twenty-six studies were located. Among the twenty-two studies on birth weight, eleven were on mean birth weight, nine on low birth weight (LBW), and four on intrauterine growth retardation (IUGR). Combined analysis of mean birth weigh study results showed a significant decrease in birth weight of nearly 43g among newborns of the heaviest caffeine-consuming mothers. LBW, IUGR, and preterm delivery displayed significant homogeneity in the test results, indicating that a pooled estimate should not be taken as an adequate measure. The high heterogeneity of the available literature on the effects of caffeine on LBW, IUGR, and preterm delivery prevents estimation of reliable pooled estimates through meta-analysis. Further assessment of caffeine intake during pregnancy is needed in future research. Foram rastreadas as publicações epidemiológicas de 1966 a 1995 sobre a associação entre cafeína e peso ao nascer e duração da gestação humana através de pesquisa em Medline. Cada estudo foi tratado como uma categoria de uma variável e seu peso foi proporcional ao inverso de sua variância. Foram localizados vinte e seis estudos. Entre os vinte e dois estudos sobre peso ao nascer, onze foram sobre peso médio ao nascer, nove sobre baixo peso ao nascer (BPN) e quatro sobre retardo do crescimento intra-uterino (RCIU). O efeito agregado sobre o peso médio ao nascer mostrou uma redução estatisticamente significativa de 43 gramas entre os recém-nascidos de mães que consumiam maiores quantidades de cafeína. A análise agregada do efeito sobre BPN, RCIU e nascimentos pré-termos apresentou teste de homegeneidade estatisticamente significativo, indicando que uma estimativa combinada não seria confiável. A grande heterogeneidade da literatura disponível quanto ao efeito da cafeína sobre o BPN, RCIU e partos pré-termo não permite o cálculo confiável de estimativas agrupadas através de meta-análise. Torna-se necessária uma avaliação mais cuidadosa do consumo de cafeína durante a gestação em estudos futuros.